Internal Control System Analysis of Merchandise Supply at PT. Indomarco Prismatama (Indomaret) Wr. Supratman South Tangerang - Krisdiana Krisdiana; Muhamad Saddam; Hasbu Naim Syaddad; Dadang Yudih; Nur Ainiyah Dini Rizky (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
The research aims to analyze internal control procedures for merchandise inventory at PT Indomarco Prismatama (Indomaret) WR Supratman, South Tangerang. In this study using a type of qualitative descriptive research that is by describing the object of research at the current state based on the facts as they are, then analyzed and interpreted, the form is in the form of surveys and developmental studies. And based on the analysis carried out, it was found that the procedure for inventory of merchandise at PT. Indomarco Prismatama (Indomaret) WR Supratman South Tangerang is not good enough, where in the process of issuing goods the clerk only receives proof of the number of goods ordered and when distributing merchandise the warehouse clerk does not record real time or update the stock of the number of goods to be distributed.